131k views
0 votes
When p2 – 4p is subtracted from p2 + p – 6, the result is . To get p – 9, subtract from this result.

User Hitomi
by
5.1k points

2 Answers

3 votes

Answer:

PLATO

Explanation:

When p2 – 4p is subtracted from p2 + p – 6, the result is . To get p – 9, subtract-example-1
User Praesagus
by
4.9k points
0 votes

Answer:

When p2 – 4p is subtracted from p2 + p – 6, the result is:

p2+p-6-(p2-4p)=p2+p-6-p2+4p=5p-6

To get p – 9, subtract from this result x:

5p-6-x=p-9

Solving for x:

5p-6-x+x-p+9=p-9+x-p+9

4p+3=x

x=4p+3

Answer:

1) When p2 – 4p is subtracted from p2 + p – 6, the result is 5p-6

2) To get p – 9, subtract from this result 4p+3

Explanation:

User Austin T French
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.